The “Archaeology” of Popular Culture: Common Sense and the Past - Kaźmierczak, Marek (Poznańskie Studia Slawistyczne, 2023)
This paper demonstrates the influence of common sense on the perception of facts from the past. In order to understand the mechanisms of reduction, instrumentalisation and banalisation of the Holocaust in popular culture, we need to understand the influence of common sense on the understanding and misunderstanding of the past, represented in this paper by the testimonies of the massacre of 1500 Jews in the forest of Niesłusz-Rudzica. The main premise of the paper is that common sense is the dominant form of knowledge and the description of reality, which is reproduced by the mechanisms at function in popular culture. This paper is an example of ‘archaeological’ work in this context.